2003
DOI: 10.1099/jmm.0.05070-0
|View full text |Cite
|
Sign up to set email alerts
|

NapA protects Helicobacter pylori from oxidative stress damage, and its production is influenced by the ferric uptake regulator

Abstract: The Helicobacter pylori protein NapA has been identified as a homologue of the Escherichia coli protein Dps. It is shown in this study that, like Dps, NapA is produced maximally in stationary phase cells and contributes to the ability of H. pylori to survive under oxidative stress conditions. Moreover, NapA co-localizes with the nuclear material, suggesting that it can interact with DNA in vivo. Furthermore, it is demonstrated that repression of NapA production by iron starvation was not so pronounced in a H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 37 publications
(71 reference statements)
5
104
1
Order By: Relevance
“…Nevertheless, the stationary-phase survival and morphology defects exhibited by ⌬spoT (ppGpp 0 ) mutants (138) point to the importance of maintaining ppGpp levels during entry into stationary phase. At this transition, H. pylori also induces the expression of virulence factors such as flagellin and napA, encoding a homologue of Dps (DNA protection during starvation) that is thought to protect against oxidative stress damage (48). Therefore, the stringent response pathway likely coordinates virulence factor expression with growth phase.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…Nevertheless, the stationary-phase survival and morphology defects exhibited by ⌬spoT (ppGpp 0 ) mutants (138) point to the importance of maintaining ppGpp levels during entry into stationary phase. At this transition, H. pylori also induces the expression of virulence factors such as flagellin and napA, encoding a homologue of Dps (DNA protection during starvation) that is thought to protect against oxidative stress damage (48). Therefore, the stringent response pathway likely coordinates virulence factor expression with growth phase.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…There was little or no inhibition of P nifS -Fur interaction by P napA . Cooksley et al (4) showed that napA in H. pylori is repressed by Fur but that expression is induced when the cells are grown in medium supplemented with FeCl 3 , and in a fur mutant strain napA expression did not depend on iron levels (4). In our study, the competition experiment was performed in the presence of MnCl 2 (a preferable substitute for iron, as previously described; see reference 11), which is needed for Fur-P nifS binding.…”
Section: Figmentioning
confidence: 99%
“…However, investigations in human patients found no correlation between neutrophil activation and H. pylori NapA expression, suggesting that this function may not be important clinically (64). Subsequently, the NapA protein was implicated in oxidative stress responses, as NapA-deficient H. pylori are more susceptible to oxidative damage in vitro (27). Deficiency of a range of antioxidant enzymes, including Hp-SOD, KatA, Hp-Tpx, and AhpC, results in a compensatory increase in NapA production (76), suggesting that it may function as a secondary antioxidant that becomes important when other defenses are overwhelmed.…”
mentioning
confidence: 99%